POLITICAL ASPECTS OF THE CIVIL SOCIETY AND RULE OF LAW FORMATION IN CONTEMPORARY AZERBAIJAN - Gunay Kurbanali Melikli (Сравнительная политика, 2019)
The political aspects of the formation of the civil society and the rule of law in modern Azerbaijan coincide with the general trends in the development of globalization and political processes in the modern world. The nature of the civil society formation in Azerbaijan is inseparably linked with the regional political processes. In particular, the analysis of internal political and regional processes, conducted on the basis of consideration of the legal framework and political structures of the country, the main stages of post-Soviet development, and tendencies in the development of civil society, which are mainly manifested through such forms of social life as the activities of non-governmental organizations, civic engagement, corruption and bureaucracy, authoritarianism in various echelons of power, showed that the civil society in Azerbaijan had not yet met the advanced standards of open society and democratic development. The formation of the rule of law is hampered by the regional contradictions, in particular, the Nagorno-Karabakh conflict, as well as high legal illiteracy of the population, the traditions-bound nature of the social structure, elements of corruption and authoritarianism in management at certain levels.